Ectomycorrhizas in Lycopodiopsida: their first registry and arbuscular mycorrhiza in Phlegmariurus saururus (Huperziaceae) - MARÍA GABRIELA ROMAGNOLI; MYRIAM DEL VALLE CATANIA; MARCELO DANIEL ARANA; PATRICIA LILIANA ALBORNOZ (Anais da Academia Brasileira de Ciências)
Abstract Lycophytes show no instances of ectomycorrhizas. Phlegmariurus saururus is the only Huperziaceae that grows in Comechingones biogeographic province, in sunny, exposed surficial rock crevices with poor soil development and very scarce water. As mycorrhizas improve plant fitness in natural ecosystems, it was hypothesized that P. saururus can develop multiple types of fungal symbiosis, including ectomycorrhizas. For detecting, identification and description of mycorrhizas, conventional techniques were employed, and samples of roots were cut with an ultra-microtome to obtain thin (3 µm) and ultrathin (0.1 µm) sections. Phlegmariurus saururus is the first species of Lycopodiopsida where the ectomycorrhizas are evidenced. Arbuscular mycorrhizas and septate endophytes were also found. Ectomycorrhizas can alter the anatomy and hydrophilic properties of roots, improving the adaptation of the plant hosts to habitats with a marked period of drought, as the novel Andean Comechingones habitats. The ectomycorrhizas detected in P. saururus could be considered as an adaptive mechanism related to the successful colonisation of this habitat and can undergo a significant transformation in the lifestyle of fungal symbiosis of lycophytes, which could provide important insights into this morphological and functional evolution.